MOA-2011-BLG-262Lb: A sub-earth-mass moon orbiting a gas giant primary or a high velocity planetary system in the galactic bulge - Bennett, D.; Batista, V.; Bond, I.; Bennett, C.; Suzuki, D.; Beaulieu, J.; Udalski, A.; Donatowicz, J.; Bozza, V.; Abe, F.; Botzler, C.; Freeman, M.; et al. (Institute of Physics Publishing, 2014)
We present the first microlensing candidate for a free-floating exoplanet-exomoon system, MOA-2011-BLG-262, with a primary lens mass of M host ~ 4 Jupiter masses hosting a sub-Earth mass moon. The argument for an exomoon hinges on the system being relatively close to the Sun. The data constrain the product ML p rel where ML is the lens system mass and prel is the lens-source relative parallax. If the lens system is nearby (large prel), then ML is small (a few Jupiter masses) and the companion is a sub-Earth-mass exomoon. The best-fit solution has a large lens-source relative proper motion, µrel = 19.6 ± 1.6 mas yr-1, which would rule out a distant lens system unless the source star has an unusually high proper motion. However, data from the OGLE collaboration nearly rule out a high source proper motion, so the exoplanet+exomoon model is the favored interpretation for the best fit model. However, there is an alternate solution that has a lower proper motion and fits the data almost as well. This solution is compatible with a distant (so stellar) host. A Bayesian analysis does not favor the exoplanet+exomoon interpretation, so Occam's razor favors a lens system in the bulge with host and companion masses of and Mhost = 0.12 ?0.06+0.19 M? and mcomp = 18 ?10+28M?, at a projected separation of a perp; = 0.84?0.14+0.25 AU. The existence of this degeneracy is an unlucky accident, so current microlensing experiments are in principle sensitive to exomoons. In some circumstances, it will be possible to definitively establish the mass of such lens systems through the microlensing parallax effect. Future experiments will be sensitive to less extreme exomoons. © 2014. The American Astronomical Society. All rights reserved.